Thinking Styles Of Secondary School Students-a Field Study On A Sample Of Students Of Ibn Al-aghlab Al-tamimi High School In M’sila - benmansour, hadda; barkat, abdelhak (El Omda in Linguistics and Discourse Analysis, 2023)
This study aimed to identify the most used thinking methods by secondary school students, as well as to identify whether there are statistically significant differences in thinking styles due to the study variables (gender, specialization, and academic level). The study was conducted on a sample of (121) male and female students who studied regularly during the first semester of the academic season: 2021/2022. The study relied on the list (Sternberg & Wagner, 1992) of thinking styles (short list) after confirming its scientific weight in the Algerian environment. The results of the study showed that most of the thinking styles are prevalent among secondary school students. As well as the absence of significant differences in most of the thinking styles of secondary school students due to the variable (gender, specialization, and academic level).